The Role of Intertextual Thesaurus in Teacher Professional Training - E. R. Yadrovskaya; A. I. Dunev (Высшее образование в России, 2024)
In the educational process, a teacher of any specialization deals with texts in oral and written form and carries out all types of speech activities. The article is devoted to the problem of studying the intertextual thesaurus of a student at a pedagogical university. An analysis of scientific publications showed the absence in the modern scientific paradigm of studies in which a quotation would be considered as a tool for transmitting a cultural code transmitted from teacher to student. A new aspect of the study of the influencing functions of quotation and the use of literary quotation as a means of studying the intertextual thesaurus of a linguistic personality determines the relevance of our research.The authors set a goal to identify and describe the intertextual thesaurus of a modern student of a pedagogical university in the context of professional training based on knowledge and mastery of literary quotations from the works of the school curriculum. 1008 students of a pedagogical university studying at different faculties took part in the experiment. The methodological foundations of the study were the theory of problem-based learning, the doctrine of linguistic personality, the system of literary development and the theory of the development of the reader’s interpretive activity, a description of precedent phenomena. When conducting the research at different stages, the method of pedagogical observation, contextual analysis of dictionaries, analysis of scientific works, a comprehensive survey, and the method of introspection were used.As a result of the experiment, it was revealed that more than 50% of university respondents were unable to identify quotes from works of art in the school curriculum. Based on the analysis of works, “negative” strategies for interpreting a literary quotation (primitivization, lowering the stylistic register of the text, transferring content to the everyday level) and positive ones (strategy of searching for value meanings, strategy of logical explanation; strategy of concretizing the content) were identified.In the course of analyzing the problem, the authors turn to the situation of school literary education and the problem of the cultural attitudes of the future teacher.